Risk Factor for Residue After Uterine Artery Chemotherapy and Embolization in Combination with Dilatation and Curettage for Treating Caesarean Scar Pregnancy - Cheng, Feng; Shan, Dan; Guo, Sijia; Cheng, Shuang; Yang, Hongwei; Han, Jialin; Hu, Tongxiu (Current Molecular Medicine, 2019)
Objective: We aimed to investigate the potential risk factors for residual lesions after uterine artery chemotherapy and embolization (UACE) in combination with dilatation and curettage (D) in patients with cesarean scar pregnancy (CSP). Settings: Retrospective case-control study. Method: Univariate analysis and logistic analysis were applied to analyze these data to assess the risk factor of residue after UACE in combination with D Results: Gestational age, human chorionic gonadotropin (HCG) level, and the gestation sac (GS) evagination to the bladder were the risk factors for the postoperative lesion. The most relevant was GS evagination to the bladder, followed by the preoperative HCG level and the gestational age. We defined the cut-off value of gestational age as 28 days with a sensitivity and specificity of 100 and 0, respectively. Conclusion: In cases with GS evagination to bladder and HCG of >28,113.65 mIU/ml as well as a gestational age of >28 days, the possibility of residual lesions was high.
Keywords: Caesarean scar pregnancy